A cross-cultural study of unwillingness to consume insects in Croatia, Lithuania, Portugal, Romania, and Mexico - Mariscal-Moreno, Rosa María; Escalante-Aburto, Anayansi; Ozuna, César; Guiné, Raquel; Chuck-Hernández, Cristina; Sarić, Marijana Matek; Bartkiene, Elena; Tarcea, Monica; Rodríguez-Sifuentes, Lucio (Frontiers in Nutrition, 2025)
IntroductionInsects are a nutritious and environmentally sustainable alternative to traditional animal proteins. Because of this, their use as human food is being implemented in Europe, although this practice is not well-received in the countries of that continent. On the other hand, there are countries like Mexico, with a long tradition of insect consumption, which can serve as a model for increasing insect consumption in European countries.MethodsA survey on insect consumption was conducted in Mexico, Croatia, Lithuania, Portugal, and Romania, and focused on people who had never consumed insects. The Chi-square test was performed for demographic variables; multinomial logistic regressions were used to establish relations between sociodemographic variables and respondents who had not consumed insects. Data from surveyed individuals from Mexico who have not included insects in their diet were analyzed to propose strategies to boost insect consumption in European countries.Results and discussionThe percentage of respondents who had not consumed insects in Mexico was 29.7%, whereas in European countries, it ranged from 70.5 to 89.3%. The Chi-square test revealed a statistically significant difference for all analyzed sociodemographic factors. Gender, age, educational level, geographical area, and income all influenced a person to be a non-consumer of insects. We suggest using isolated insect protein or insect flour to formulate/develop food products, inform about the nutritional and health benefits of insects, integrate insects into the countries’ traditional cuisine, and reduce the costs of insects to increase their consumption in European countries.